2019
DOI: 10.1245/s10434-019-07644-w
|View full text |Cite
|
Sign up to set email alerts
|

Standard Operating Procedures for Anesthesia Management in Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy Improve Patient Outcomes: A Patient Cohort Analysis

Abstract: Main Text: Abbreviations CRS Cytoreductive surgery HIPEC Hyperthermic intraperitoneal chemotherapy PCI Peritoneal Cancer Index CC-Score Completeness of Cytoreduction Score DPAM Diffuse peritoneal adenomucinosis PMCA Peritoneal mucinous carcinomatosis CRC Colorectal Carcinoma SOP Standard operating procedure 3 / 20 SYNOPSIS We assessed the role of standard operating procedures (SOPs) for anesthesia management in a cohort of patients after CRS/HIPEC. Introduction of SOPs improved extubation rates, and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Other authors have reported OTLs between 360 and 625 minutes [8,18]. The median OTL in this study population was 400 mins and was significantly longer in the group with AEs than in the group without AEs (440 mins vs. 370 mins, p <0.001).…”
Section: Operative Time Lengthmentioning
confidence: 42%
See 1 more Smart Citation
“…Other authors have reported OTLs between 360 and 625 minutes [8,18]. The median OTL in this study population was 400 mins and was significantly longer in the group with AEs than in the group without AEs (440 mins vs. 370 mins, p <0.001).…”
Section: Operative Time Lengthmentioning
confidence: 42%
“…Over the last decades, cytoreductive surgery (CRS) combined with hyperthermic intraoperative chemotherapy (HIPEC) has evolved as an effective multimodal treatment for selected patients with peritoneal surface malignancies of different origins [3][4][5][6][7]. As any complex procedure, it requires a multidisciplinary and dedicated team and a standard perioperative approach, which includes appropriate patient selection, preoperative optimization, intraoperative protocol, and adequate postoperative care to improve outcomes [8,9]. The creation and management of such meticulous groundwork can only be justified by an increase in quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative findings revealed an average PCI score of 12 , intraabdominal ascites measured 150 (0-3000) mL, average body temperature was 36.1°C (35)(36)(37), average lactate levels were 3 (2-7) mmol/L, Pao2/fio2 was measured as 3.3 (2.4-4.1) mm Hg, mean arterial pressure (MAP) was 60 (55-70), average surgery duration was 6.5 hours (3-14), and average blood loss was 400 (200-4000) cc. The ICU stay duration was 1.5 days (0-20), and the average hospital stay was 8.8 days (4-46).…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that monitoring and maintaining diuresis at physiological levels might be as effective as sophisticated measurement of volume status. [35] Colantonio et al conducted a single-center prospective randomized study that compared GDFT with standard care in 80 patients who underwent CRS and HIPEC. In their study, patients in the control group received crystalloid infusions ranging from 4 mL/kg/h to 10 mL/kg/h, whereas those in the GDFT group received a baseline rate of 4 mL/kg/h with subsequent colloid boluses based on physiological variables.…”
Section: Discussionmentioning
confidence: 99%
“…Although these physiologic perturbations inherent to the procedure represent a significative perioperative challenge, to date no standard guidelines exist concerning intraoperative management. The use of goal-directed therapy enables to individually adjust the fluid therapy, avoiding over-hydration and ensuring hemodynamic stability of patients, resulting in lower morbidity and mortality rates, as well as length of hospital stay [ 54 , 55 , 56 , 57 ]. The procedure often includes complex, multivisceral resections and blood loss is significant in the great majority of patients.…”
Section: Discussionmentioning
confidence: 99%